PENGARUH HEALTH EDUCATION TERHADAP PERILAKU WANITA USIA SUBUR (WUS) DALAM PEMERIKSAAN IVA PADA DETEKSI DINI KANKER SERVIKS DI PUSKESMAS KASSI-KASSI KOTA MAKASSAR - Sri Sudarwaty; Een Kurnaesih; Reza Aril Ahri (LPPM STIK Makassar, 2018)
Influence of Health Education on Female Age Behavior (WUS) in IVA Examination in Early Detection of Cervical Cancer at Kassi-Kassi Health Center of Makassar (Guided Een Kurnaesih and Reza Aril Ahri). Currently, the coverage of early detection of cervical cancer is still very low, due to a lack of knowledge and public awareness to participate in the early detection of cervical cancer programs. IVA examination is an early detection program for cervical cancer applied by the government. The purpose of this study is to know the influence of Health Education on the Behavior of Women Aged Fertile (WUS) in IVA Examination on Early Detection of Cervical Cancer at Kassi-Kassi Health Center of Makassar City The research design used was a quasi-experimental pre-post design with a comparison group which attempted to reveal the effectiveness of the independent variable to the dependent variable by stretching the control group in addition to the experimental group with the number of samples 66 Wus. The result of the research shows that health education influences knowledge, attitude, and action of WUS in IVA examination on early detection of cervical cancer at Kassi-Kassi Health Center Makassar 2018, from T-Test statistic test p sig = 0,000 <0,05. Health Education in the IVA examination in the early detection of cervical cancer gives the effect of increasing knowledge, attitude, and action to become more positive, it is expected the authorized institution can do it in a wider range and better quality